INNOVATIVE ACTIVITIES OF SMALL AND MEDIUM-SIZED ENTERPRISES: CURRENT REALITIES - KUCHER, Marharyta; ZHYDYK, Andriy; TOVT, Yurii; STRILETS, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the activities of small and medium-sized enterprises in innovative development. It was established that the innovative activity of small and medium-sized enterprises is an important determinant of their development. The main problems of innovative activity of small and medium-sized enterprises, taking into account modern business conditions, have been identified. The main reasons for the importance of innovations for modern business are given and it is indicated how they can be implemented in modern conditions. The innovative activity of small and medium-sized enterprises (SMEs) is of great importance for the economy of any country. It contributes to the creation of new jobs, the development of competitiveness and the growth of GDP. Innovations allow SMEs to introduce new technologies, improve products and services, which contributes to their development and increased profits. The current state of innovative development of small and medium-sized businesses varies from country to country. In a number of developed countries, such as the USA and European countries, innovation support is aimed at stimulating SMEs through grants and tax breaks for research and development. However, in many countries, the development of innovation in SMEs faces barriers such as lack of funding, limited availability of technology and insufficient qualification of personnel. Each country has its own unique challenges and opportunities for developing the innovative potential of SMEs. Today, Ukraine is actively working on the development of innovations in the sector of small and medium-sized businesses. Government policy is aimed at stimulating innovation in SMEs by creating favorable conditions for business development, facilitating access to financial resources, technologies and improving staff qualifications. However, there are challenges such as bureaucratic obstacles, insufficient funding and limited access to the latest technologies that inhibit the innovative development of SMEs in Ukraine. Innovative development of the enterprise is extremely relevant in the modern world. Rapid changes in technology, market conditions and increased competition put businesses under constant pressure and the need to improve. Innovations allow enterprises to develop new products and services, reduce costs, improve the quality of products and services, thereby ensuring their competitiveness in the market. In addition, innovation helps attract new customers, expand business and increase profitability. Thus, innovative development plays a key role in ensuring the success of the enterprise in modern conditions.
Keywords: innovations; innovative activity; innovative development; competitiveness; small and medium-sized enterprises